Factors which predict adverse events following surgery in adults with cervical spinal deformity. (1st April 2021) - Varshneya, Kunal; Jokhai, Rayyan; Medress, Zachary Adam; Stienen, Martin Nikolaus; Ho, Allen; Fatemi, Parastou; Ratliff, John Kevin; Veeravagu, Anand
Abstract : Aims: The aim of this study was to identify the risk factors for adverse events following the surgical correction of cervical spinal deformities in adults. Methods: We identified adult patients who underwent corrective cervical spinal surgery between 1 January 2007 and 31 December 2015 from the MarketScan database. The baseline comorbidities and characteristics of the operation were recorded. Adverse events were defined as the development of a complication, an unanticipated deleterious postoperative event, or further surgery. Patients aged < 18 years and those with a previous history of tumour or trauma were excluded from the study. Results: A total of 13, 549 adults in the database underwent primary corrective surgery for a cervical spinal deformity during the study period. A total of 3, 785 (27.9%) had a complication within 90 days of the procedure, and 3, 893 (28.7%) required further surgery within two years. In multivariate analysis, male sex (odds ratio (OR) 0.90 (95% confidence interval (CI) 0.8 to 0.9); p = 0.019) and a posterior approach (compared with a combined surgical approach, OR 0.66 (95% CI 0.5 to 0.8); p < 0.001) significantly decreased the risk of complications. Osteoporosis (OR 1.41 (95% CI 1.3 to 1.6); p < 0.001), dyspnoea (OR 1.48 (95% CI 1.3 to 1.6); p < 0.001), cerebrovascular accident (OR 1.81 (95% CI 1.6 to 2.0); p < 0.001), a posterior approach (compared with an anterior approach, OR 1.23 (95% CI 1.1 to 1.4); p < 0.001), and the use of bone morphogenic protein (BMP) (OR 1.22 (95% CI 1.1 to 1.4); p = 0.003) significantly increased the risks of 90-day complications. In multivariate regression analysis, preoperative dyspnoea (OR 1.50 (95% CI 1.3 to 1.7); p < 0.001), a posterior approach (compared with an anterior approach, OR 2.80 (95% CI 2.4 to 3.2; p < 0.001), and postoperative dysphagia (OR 2.50 (95% CI 1.8 to 3.4); p < 0.001) were associated with a significantly increased risk of further surgery two years postoperatively. A posterior approach (compared with a combined approach, OR 0.32 (95% CI 0.3 to 0.4); p < 0.001), the use of BMP (OR 0.48 (95% CI 0.4 to 0.5); p < 0.001) were associated with a significantly decreased risk of further surgery at this time. Conclusion: The surgical approach and intraoperative use of BMP strongly influence the risk of further surgery, whereas the comorbidity burden and the characteristics of the operation influence the rates of early complications in adult patients undergoing corrective cervical spinal surgery. These data may aid surgeons in patient selection and surgical planning. Cite this article: Bone Joint J  2021;103-B(4):734–738.